2005
DOI: 10.4161/cc.4.11.2169
|View full text |Cite
|
Sign up to set email alerts
|

ATR Activation Necessary But Not Sufficient for p53 Induction and Apoptosis in Hydroxyurea-Hypersensitive Myeloid Leukemia Cells

Abstract: Hydroxyurea (HU) is a competitive inhibitor of ribonucleotide reductase that is used for the treatment of myeloproliferative disorders. HU inhibits DNA replication and induces apoptosis in a cell type-dependent manner, yet the relevant pathways that mediate apoptosis in response to this agent are not well characterized. In this study, we employed the human myeloid leukemia 1 (ML-1) cell line as a model to investigate the mechanisms of HU-induced apoptosis. Exposure of ML-1 cells to HU caused rapid cell death t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Furthermore, it has been reported that hydroxyurea treatment induces transcription factors such as p53 [36], which alters the transcription activity of certain types of proteins [37]. However, hydroxyurea had little effect on the expression level of GL3, stably expressed in HeLa cells under the regulation of the CMV promoter ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that hydroxyurea treatment induces transcription factors such as p53 [36], which alters the transcription activity of certain types of proteins [37]. However, hydroxyurea had little effect on the expression level of GL3, stably expressed in HeLa cells under the regulation of the CMV promoter ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Among the two possibilities, the latter seems likely because cell cytotoxicity analysis revealed correlation between pATR induction and cell death during KU + Dox treatments pointing out to a pathway involving KU ┤ ATM = pATR → Apoptosis. As such, the role of ATR in apoptosis induction has already been reported following treatments with chemotherapeutic agents [78,79].…”
Section: Time Dependent Treatment Of 100nm Doxorubicin Demonstrated Cmentioning
confidence: 93%
“…ATR activity has already been known to signal apoptosis in response to treatments with different chemotherapeutic agents [78,79]. Hence the inhibitory state of ATR levels at lower DNA damage suggests cellular signalling preference towards DNA repair.…”
Section: Analysis Of the Mathematical Models Of Ddrmentioning
confidence: 99%
“…Similar to ATR, loss of Chk1 function results not only in mouse embryonic lethality at the developmental early stage but also causes cells to bypass the DNA damage and DNA replication checkpoints (33,35). p53 is also very well known to be important to maintain cell cycle fidelity, and ATR phosphorylates p53 at Ser 15 and Ser 37 (32,36). These data indicate that ATR, Chk1, and p53 are crucial for maintaining genomic integrity via regulation of the cell cycle in normal cells and in cells with damaged DNA.…”
Section: Discussionmentioning
confidence: 99%
“…IR is a well-known inducer of DNA double strand break. Hydroxyurea, a competitive inhibitor of ribonucleotide reductase, blocks DNA replication, resulting in ATR activation (13,32). HCT116-Mock and HCT116-COX-2 cells were exposed to graded doses of IR or hydroxyurea, and then cell viability was monitored by a clonogenic assay.…”
Section: Hct116-cox-2 Cells Containing Elevated Atr Are Resistant To mentioning
confidence: 99%